Pengatur Kelembaban dan Suhu Kumbung Jamur Tiram Otomatis Menggunakan Mikrokontroller Atmega328 dengan Logika Fuzzy Berbasis Iot - Muhammad Abi Muzaki; Rakhmat Kurniawan; Muhammad Siddik Hasibuan (VISA: Journal of Vision and Ideas, 2024)
Fungi live by taking other products from dead organisms and usually only grow in moist places. It is known that the living environment of mushrooms can grow well at a temperature of 16°C - 30°C with a humidity of 80 - 95%. there are several obstacles for mushroom cultivators in oyster mushroom cultivation, seeing changes in temperature and humidity that often occur to increases and decreases in temperature and humidity can occur at any time. To make it easier for farmers to monitor changes in temperature and humidity in mushroom kumbung, an automatic control system is needed that can provide information related to temperature and humidity in real time and when the temperature and humidity are not appropriate, the control system can help maintain temperature and humidity by spraying water, the system This control uses the Atmega328 Microcontroller as a data processor. This control system is designed using fuzzy logic which is expected to help provide the best temperature and humidity in the mushroom kumbung area by using a DHT11 sensor to detect temperature and humidity, and the help of ESP8266 which was developed into an Internet of things to make it easier to monitor temperature and humidity. in real time. In this study, the fuzzy Sugeno method is used because this method is suitable for finding temperature and humidity levels that often change. With this fuzzy logic method, a mathematical circuit is obtained which is used to represent ambiguity, and lack of information.